Reactivation of Tuberculosis Following Major Abdominal Surgery - Jha, Abhishek A.; Ballal, Rajesh; K., Aditya G. (Journal of Health and Allied Sciences NU, 2016)
A 46 year old male presented with dysphagia to solids and vomiting. He was evaluated clinically, radiologically and by upper GI endoscopy. He was diagnosed to have carcinoma of the distal 1/3rd of the oesophagus extending onto the Fundus of stomach (Sievert III).A standard transhiatalesophagectomy and total gastrectomy with Roux-en-Y esophagesophageal reconstruction was done. His post op period was relatively uneventful and discharged on POD 22. He was readmitted for radiotherapy as per Protocol. (5040 cGY/25#/5 weeks). He developed persistent cough with expectoration on day 5. A pulmonology consult was given and sputum for AFB was sent. He was tested positive for pulmonary tuberculosis.This man had a significant past history of being treated for TB meningitis 20 years ago. Treatment now was started as per DOTS regimen and was discharged after his course of radiotherapy. His Antitubercular drug therapy has been continued.A search of the English literature survey revealed no similar articles of “Reactivation of Tuberculosis after abdominal surgery”. The possible mechanism may be due to profound immunosuppression following malignancy and its treatment.It is worthwhile to consider Tuberculosis as a differential diagnosis in the appropriate clinical setting as a cause of unexplained fever.
Keywords: Key words are TB; Tuberculosis; LTBI; Latent Tuberculosis Infection; DOTS; Directly Observed Treatment Short Course; AFB: Acid Fast Bacilli